FORMULASI DAN UJI EFEKTIVITAS PATCH ANTIPIRETIK EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava L) PADA TIKUS PUTIH - Beama, Christin Aprillian; Poso, Maria Carolinda (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Guava leaves (Psidium guajava L) are one of the traditional medicines empirically used by the community in Indonesia for fever treatment. Guava leaves (Psidium guajava L) contain several compounds, one of which is flavonoids, which play a role in antipyretic activity. This study aims to determine the effectiveness of the formulation of guava leaf extract patches (Psidium guajava L) in reducing fever in white rats, and to identify the most effective concentration of the guava leaf extract patch formulation (5%, 10%, and 15%) in lowering fever in white rats. This study used a True Experimental Design (Posttest-Only Control Design). The test subjects in this study were 25 white rats divided into 5 groups. The positive control group was given a